Anxiety and Depression in Patients with HIV Encephalopathy (Eurasian Medical Research Periodical, 2023)
This article examines the level of anxiety and the degree of depression in patients with HIV-associated encephalopathy. The patients were examined using the State-Trait Anxiety Inventory (STAI) and the Hamilton Depression Scale .